2011
DOI: 10.1186/1556-276x-6-172
|View full text |Cite
|
Sign up to set email alerts
|

Hf-based high-k materials for Si nanocrystal floating gate memories

Abstract: Pure and Si-rich HfO2 layers fabricated by radio frequency sputtering were utilized as alternative tunnel oxide layers for high-k/Si-nanocrystals-SiO2/SiO2 memory structures. The effect of Si incorporation on the properties of Hf-based tunnel layer was investigated. The Si-rich SiO2 active layers were used as charge storage layers, and their properties were studied versus deposition conditions and annealing treatment. The capacitance-voltage measurements were performed to study the charge trapping characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…The formation of crystallized Si-ncs upon an annealing at 1100°C can be easier distinguished (Fig.1a). It is worth to note that recently we showed that similar Si-richSiO 2 materials demonstrate bright emission in red-near infrared spectral range and its appearance is accompanied by the formation of amorphous Si-ncs (18). However, the Sincs were found to be amorphous when annealed at T A <1100°C (24).…”
Section: Resultsmentioning
confidence: 96%
“…The formation of crystallized Si-ncs upon an annealing at 1100°C can be easier distinguished (Fig.1a). It is worth to note that recently we showed that similar Si-richSiO 2 materials demonstrate bright emission in red-near infrared spectral range and its appearance is accompanied by the formation of amorphous Si-ncs (18). However, the Sincs were found to be amorphous when annealed at T A <1100°C (24).…”
Section: Resultsmentioning
confidence: 96%
“…Consequently, the formation of Si-ncs can occur due to decomposition of the SiO x phase, similar to that observed for Si-richSiO 2 materials. 9,19 It is worth to note that for HfSiO materials with about 20 at. % of Hf content, the formation of HfO 2 -rich and SiO 2 -rich phases occurred only upon post-deposition processing.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7] Widespread applications of high-j materials are linked with the floating gate non-volatile memory devices containing semiconductor and/or metallic nanocrystals (NCs) or amorphous nanoclusters (ncs). 8,9 Their controlled precipitation in high-j oxide host is a major challenge for such devices.…”
Section: Introductionmentioning
confidence: 99%
“…1 Compared to semi-conductive (Si,Ge) 2,3 and organic (C, graphene) 4,5 charge storage candidates, noble metal nanoparticles (Pt, 6 Au 7 and Ag 8 ) embedded in oxide dielectric films (Al 2 O 3 , HfO x , ZrO 2 , TiO 2 , HfAlO x ) have been highlighted due to their high work function and excellent charge properties, but they are not suitable for large-scale industrial applications due to their high cost. Ni nanocrystals (Ni-NCs) has a high work function of 5.35 eV, 9 stable chemical properties, and have been reported to exhibit a memory window width (flat-band voltage shift |∆ V FB |) ranging from 1 to 20 V, [10][11][12][13][14][15][16] showing excellent charge storage capacity.…”
Section: Introductionmentioning
confidence: 99%